2022
DOI: 10.1021/acs.iecr.2c01204
|View full text |Cite
|
Sign up to set email alerts
|

Effective Adsorptive Denitrogenation from Model Fuels over CeY Zeolite

Abstract: Nitrogen-containing compounds (NCCs) in hightemperature coal tar have a negative impact on its utilization. This work aimed to prepare a series of Ce x Y adsorbents with superior capacity and selectivity by ion exchange, and further clarify the regeneration properties and adsorption mechanism. The adsorptive denitrogenation properties were evaluated at different temperatures using batch adsorption experiments in different model fuels. The implication of Ce loading on the adsorption properties has been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Zhang et al had previously reported that a Cuexchanged Y zeolite could adsorb ~50% more DBT than the pristine adsorbent, and the adsorption of SCCs using d-block metal exchanged Y zeolites mainly occurs through π complexation [81], which could explain the simultaneous deep ADN/S. Zhang et al studied the effect of ion-exchanged Y zeolite with cerium [82] on ADN, since it was previously reported that the incorporation of La 3+ species into aluminosilicate positively affected its sulfur adsorption capacity due to the introduction of the possibility for direct interactions between the lanthanum ions and the adsorbents [83,84]. The researchers found that increasing the amount of Ce in the adsorbent did not necessarily imply an increase in denitrogenation efficiency (Figure 5).…”
Section: Zeolitesmentioning
confidence: 99%
“…Zhang et al had previously reported that a Cuexchanged Y zeolite could adsorb ~50% more DBT than the pristine adsorbent, and the adsorption of SCCs using d-block metal exchanged Y zeolites mainly occurs through π complexation [81], which could explain the simultaneous deep ADN/S. Zhang et al studied the effect of ion-exchanged Y zeolite with cerium [82] on ADN, since it was previously reported that the incorporation of La 3+ species into aluminosilicate positively affected its sulfur adsorption capacity due to the introduction of the possibility for direct interactions between the lanthanum ions and the adsorbents [83,84]. The researchers found that increasing the amount of Ce in the adsorbent did not necessarily imply an increase in denitrogenation efficiency (Figure 5).…”
Section: Zeolitesmentioning
confidence: 99%